ANALISIS LAPORAN KEUANGAN SEBAGAI DASAR PENILAIAN KINERJA KEUANGAN PERUSAHAAN PADA PT BIMA SAKTI PERTIWI TBK - Pakpahan, Yola Ekklesia; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The purpose of this research is to discover financial performance of PT Bima Sakti Pertiwi Tbk for the year 2014 up to 2018 using analysis of liquidity, solvency, profitability and activity. This type of research is conducted in the form of secondary data which the data is from financial reports. The data collection technique used was the observation method and the documentation method. The data analysis technique used is to calculate the liquidity ratio, solvency, profitability and activity. Based on the results of the analysis of the financial data of PT Bima Sakti Pertiwi Tbk, it is concluded that the level of liquidity in 2014 to 2018 which is viewed from the current ratio is not good, then the quick ratio is not good and the cash ratio is not good. The level of solvency in 2014 to 2018 in terms of DAR and DER showed unfavorable results. The level of profitability in 2014 to 2018 in terms of GPM, ROA, ROE and NPM showed unfavorable results. The level of activity in 2014-2018 in terms of ITO, TATO and WCTO showed poor results. Judging from the calculation of the analysis of liquidity ratios, solvency, profitability and activity, it is said that the financial performance of PT Bima Sakti Pertiwi needs to be improved again.Â Keywords: liquidity, solvency profitability and activityÂ Â